THE ROLE OF INNOVATIVE TECHNOLOGIES, SOCIAL MEDIA ALGORITHMS, AND EHEALTH LITERACY IN SHAPING HEALTH-SEEKING BEHAVIOR AMONG ADOLESCENTS AND YOUNG ADULTS WITH POLYCYSTIC OVARY SYNDROME (PCOS): A SYSTEMATIC REVIEW - Karolina Julia Hak; Karolina Magda Leszczyńska; Maciej Tomasz Wieczorek; Alicja Maria Mitan; Aleksandra Maria Tomaszewska; Kamila Teresa Kańska; Karolina Krawczyk; Jeremi Leon Jasiński; Anna Krzysztofik; Weronika Napierała (International Journal of Innovative Technologies in Social Science, 2026)
Background: Polycystic Ovary Syndrome (PCOS) is a highly prevalent, complex endocrine and metabolic disorder that profoundly alters the physiological and psychological landscape of adolescent development. Driven by systemic clinical dissatisfaction, chronic invalidation, and a lack of tailored institutional support, the modern patient experience has rapidly transitioned from traditional, clinic-based management to hyper-connected digital self-management.Objective: This systematic review aims to comprehensively explore how innovative digital technologies—specifically algorithmic social media platforms (TikTok, Instagram, YouTube, X), the Internet of Things (IoT), and machine-learning-analyzed discussion forums (Reddit)—shape the health-seeking behaviors and medical decision-making of women diagnosed with PCOS. Furthermore, it evaluates the critical mediating role of electronic health (eHealth) literacy.Methodology: A systematic synthesis was conducted in strict accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Electronic databases (PubMed/MEDLINE, Google Scholar, Scopus) were systematically searched for peer-reviewed studies published between 2012 and 2026. The synthesis integrated qualitative sociological interviews, mixed-methods intervention studies, natural language processing (NLP) sentiment analyses, and big data infodemiology (total n=23).Results: The synthesis reveals a critical, high-stakes dichotomy. While digital platforms and IoT applications are essential for identity reconstruction ("sense-making") and peer support, they are simultaneously potent vectors for unregulated health misinformation. Visual algorithms heavily promote unverified, "root-cause" supplements and restrictive diets, overshadowing evidence-based medicine. The reliance on digital crowdsourcing for interpreting laboratory results introduces unprecedented friction into the patient-physician dynamic. However, emerging evidence indicates that targeted, evidence-based Digital Health Interventions (DHIs) and higher baseline eHealth literacy significantly mitigate these risks, leading to improved clinical and psychological outcomes.Conclusion: The integration of digital health literacy into routine endocrine and gynecological care is no longer optional. Healthcare providers must recognize social media as a primary, foundational diagnostic ecosystem. Addressing this requires active clinical mediation, the co-development of evidence-based digital interventions, and profound clinical empathy to help patients navigate algorithmic noise safely.